-15=t-55

Simple and best practice solution for -15=t-55 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15=t-55 equation:


Simplifying
-15 = t + -55

Reorder the terms:
-15 = -55 + t

Solving
-15 = -55 + t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-1t' to each side of the equation.
-15 + -1t = -55 + t + -1t

Combine like terms: t + -1t = 0
-15 + -1t = -55 + 0
-15 + -1t = -55

Add '15' to each side of the equation.
-15 + 15 + -1t = -55 + 15

Combine like terms: -15 + 15 = 0
0 + -1t = -55 + 15
-1t = -55 + 15

Combine like terms: -55 + 15 = -40
-1t = -40

Divide each side by '-1'.
t = 40

Simplifying
t = 40

See similar equations:

| 1x-16=40-3x | | 15+(3x-12)-(4x+5)-(6x+1)=6 | | -e/95+6=4 | | -184-8x=86+2x | | 5(x-2x)=5-5x+3 | | X^2-4X-20= | | -n/1.6+7.9=8.4 | | X^2-4-20= | | 16-10x=-2x | | -v/7+8=19 | | A+17=43 | | 14+a=3x+xb | | 4x-20+12=584 | | .006(x+2)=.007x+.009 | | -k/9+6=-4 | | 4x+89=-7x-164 | | -23-5x=10x+16 | | -132=3x+3(-7x-2) | | 11(m-2)=0 | | -6y+6=7y+9 | | 2(x+4)=-5+1 | | -70+2x=-4x+32 | | 100-(x+2)=x/2 | | 75=-3(-6n-5) | | 256x^2-225= | | -3(x+2)+4(3x-8)=2(4x+7)+2(3x-6) | | -55-12x=-5x+36 | | (4x+9)(x-7)= | | 2(x+4)=-5x | | 2x+4=-5x+1 | | 49n^2-81=0 | | 100=(x+2)+(x/2) |

Equations solver categories